Effect of diabetes on exosomal miRNA profile in patients with obesity. Issue 1 (3rd September 2020) - Kim, Hyoshik; Bae, Yun-Ui; Lee, Haekyung; Kim, Hyoungnae; Jeon, Jin Seok; Noh, Hyunjin; Han, Dong Cheol; Byun, Dong Won; Kim, Sang Hyun; Park, Hyeong Kyu; Ryu, Seongho; Kwon, Soon Hyo
Abstract : Introduction: Obesity is a risk factor for type 2 diabetes mellitus (T2DM) and cardiovascular disease. T2DM increases the risk of cardiovascular-related death. We investigated changes in circulating exosomal microRNA (miRNA) profiles in patients with DM with obesity compared with patients without DM with obesity. Research design and methods: This prospective study involved 29 patients with obesity (patients without DM=16, patients with DM=13) and healthy volunteers (HVs) (n=18). We measured circulating levels of exosomal miRNAs by next-generation sequencing and compared miRNA levels across the three groups. Results: The expression levels of 25 miRNAs (upregulated=14, downregulated=11) differed between patients with obesity with DM and patients with obesity without DM. Compared with HV, patients with DM with obesity had 53 dysregulated miRNAs. Additionally, moving stepwise from HV to patients with obesity without DM to patients with obesity with DM, there was a consistent increase in expression levels of miR-23a-5p and miR-6087 and a consistent decrease in expressions levels of miR-6751-3p. Conclusions: Our data show that the exosomal miRNAs is altered by dysregulated glucose metabolism in patients with obesity. This circulating exosomal miRNA signature in patients with obesity with or without DM is a potential biomarker and therapeutic target in these patients.